(untitled) (Research, Society and Development, 2022)
Objective: To discuss the impact of the use of hormonal oral contraceptives on women’s sexuality. Methodology: Integrative literature review using the Scientific Electronic Library (SciELO), PUBMED and Latin American and Caribbean Literature (LILACS) databases. Results: Thematic analysis was divided into three topics: the types of hormonal oral contraceptives, hormonal changes and clinical manifestations in women and the effects of hormonal contraceptives on female sexuality. Female sexuality is influenced by several factors, both physiological and related to the environment and lifestyle. In this context, medications are also included, for example, the use of hormonal oral contraceptives, which can cause changes in the woman’s body, some that improve the quality of life of users, such as the choice of contraception, regularization of the menstrual cycle, reduction the manifestations of premenstrual tension; and others that can interfere with behavior and decrease libido, directly interfering with a woman’s sexuality.